Manifestation of Corruption in Society (Zien Journal of Social Sciences and Humanities, 2022)
Corruption as an ancient phenomenon, Corruption is an almost unresolved problem, Corruption (from Latin corruptio - spoilage, bribery), a crime consisting in the direct use by an official of the rights granted to him by position for the purpose of personal enrichment. Corruption is also called bribery of officials, their venality